[Book Review] Teaching the History of the Book, edited by Matteo Pangallo and Emily B. Todd - Lemmons, David (Teaching and Learning Inquiry, 2023)
Book review of Teaching the History of the Book, edited by Matteo Pangallo and Emily B. Todd.